Representasi Animisme & Spiritualisme dalam Tari Sintren: Kajian Komunikasi Budaya - Gunawan, Lita; Florina, Ike Desi; Edy, Sarwo (Universitas Medan Area, 2025)
This study explores the representation of animism and spiritualism in Sintren Dance through the perspective of cultural communication. Sintren is a traditional Javanese dance performance rooted in mystical beliefs, particularly involving ancestral spirits and the spirit realm. The study aims to identify the role of Sintren Dance as a medium of cultural communication that conveys deeply embedded values of animism and spiritualism. A qualitative method with an ethnography of communication approach was employed. Data were gathered through direct observation, in-depth interviews, and documentation, including photos and video recordings. The research focuses on three communities in the northern coastal region of Central Java: Paguyuban Sintren Sekar Arum (Tegal), Paguyuban Sintren Satria Nada (Brebes), and Paguyuban Sintren Satria Budaya (Pemalang). Findings reveal that Sintren functions as a symbolic channel of communication involving sacred objects (incense, chicken cages, black glasses, shawls, and flowers) that represent animism. Spiritualism is reflected in the ritual use of mantras and the belief in spirit possession, where the dancer enters a trance. The pawang acts as a spiritual intermediary, while the dalang manages the performance. The saweran tradition and audience interaction also reflect deep emotional and spiritual engagement. Ultimately, Sintren is more than entertainment—it is cultural heritage and spiritual expression that communicates ancestral values across generations.